Effect of different doping on the structural, morphological and magnetic properties for Cu doped nanoscale spinel type ferrites - ESMER, KADİR (ELSEVIER SCIENCE BV, 2013)
CuxM1-xFe2O4 (M=Co, Mn and Ni; x=0.0, 0.6 and 1.0) spinel type ferrite nanoparticles have been synthesized by cetyltrimethylammonium bromide (CTAB) assisted hydrothermal route using NaOH solution. The purity, structural characterization and magnetic properties have been investigated using the scanning electron microscopy, x-ray diffraction analysis and a quantum design vibrating sample magnetometer depending on the temperature. The scanning electron microscopy imaging exhibits very powerful aspect. The average size of composite nanoparticles for all samples was determined. Diameter of the samples is synthesized in nanoscale. The x-ray diffraction results have indicated that these samples are high phase purity, crystalline and inverse spinel ferrites. The temperature evolution of the magnetic properties and different doping effects for the samples have been observed. The pseudo spin-valve behavior has been showed for Cu0.6Co0.4Fe2O4 and CoFe2O4 samples. These samples can be considered as promising materials for magnetic recording media and electromagnetic absorbing technologies applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Nanoparticle; Spinel ferrite; Magnetic behavior; Spin-valve; ASSISTED HYDROTHERMAL SYNTHESIS; MN-ZN FERRITES; COPRECIPITATION METHOD; CATALYTIC-PROPERTIES; PRECURSOR METHOD; NICKEL FERRITE; NANOPARTICLES; COFE2O4; NIFE2O4; COBALT